Government Innovation in Social Sciences: A Literature Review - Syahnaz Oriza Keumala; Ulung Pribadi (Universitas Muhammadiyah Malang, 2021)
Government innovation has become a common concept in many countries for influencing public sector reform. Government policy has also attracted attention from academia as a modern concept of governance. This study aims to understand issue innovation in government perspective. This study reviewed the literature of an article published in the social sciences through the NVivo analysis tool. This study indicates that the main issues in government innovation are public, actors, politics, policies, and institutions. This study also finds that government innovation can be used for decision-making and increasing organizational capacity. In addition, it can also be used to improve democratic institutions and increase organizational. This article contributions is provide new topic concerning government innovation in the future.